DIAGNOSING PERFORMANCE IN GOVERNING UTILIZATION OF FOREST PRODUCTION IN FMU MERANTI–MUSI BANYUASIN, SOUTH SUMATRA - Ja Posman Napitu; Aceng Hidayat; Sambas Basuni; Sofyan Sjaf (Indonesian Journal of Forestry Research, 2019)
Perspective difference of users related to forest area utilization has caused tenurial conflicts, as well as, possible utilization conflicts. This study aimed to understand stakeholders’ interests and influences as exogenic factors that caused the non-optimal institutional performance. This study used an institutional diagnostic approach to understand how the situation and action arena is from inter-influencing institutional entities. Data collection used the convergent parallel mixed method (CPMM) approach, while analysis used the rapid land tenure assessment (RaTA) method. Further, this study used the Institutional Analysis Development (IAD) method to explain how the exogenic factors influence each other. The results showed that the characteristics of biophysical attributes, community attributes, as well as, rule in use were inter-influencing within the action arena. Besides, based on the post-prospective analysis result, policy decision opted by the government tend to not consider the community existence, who have been using the land for their livelihood. This situation has caused utilization conflicts between communities and concession holders. Thus, this study recommends: 1) the stakeholders to establish a communication forum for all parties to obtain clear information about forest utilization and to support institutional performance; 2) institutionalizing local community to govern forest utilization, and 3) determining management and concept of sustainable forest, as well as, policy making.